2008
DOI: 10.1021/bi8011675
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Lipopolypeptides Composed of Palmitoyl Di- and Tricationic Peptides: In Vitro and in Vivo Activities, Self-Assembly to Nanostructures, and a Plausible Mode of Action

Abstract: Antimicrobial lipopeptides are produced nonribosomally in bacteria and fungi during cultivation. They are composed of a cationic or an anionic peptide covalently bound to a specifically modified aliphatic chain. Most of the peptidic moieties have complex cyclic structures. Here we report that conjugation of a palmitic acid to the N-terminus of very short cationic di- and tripeptides composed of all l- and d, l-amino acids endowed them with potent antimicrobial activities. Interestingly, cell specificity was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
162
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 168 publications
(175 citation statements)
references
References 60 publications
(100 reference statements)
8
162
1
Order By: Relevance
“…Previous studies reported on a family of potent antimicrobial and antifungal ultrashort lipopeptides containing four or fewer amino acids (21,22). The conjugation of fatty acids to otherwise inactive peptides greatly increased the activity and spectrum.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies reported on a family of potent antimicrobial and antifungal ultrashort lipopeptides containing four or fewer amino acids (21,22). The conjugation of fatty acids to otherwise inactive peptides greatly increased the activity and spectrum.…”
Section: Discussionmentioning
confidence: 99%
“…Both D-and L-amino acids were used, and the sequences were based on previous studies of fatty acid-conjugated peptides (21,22). The lipophilic part of the previously studied lipopeptides consisted of a linear fatty acid, for example, palmitic acid, coupled to the N terminus of the peptide sequence.…”
Section: Design and Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…The first results in enhanced permeability, disruption, or perforation of the membrane and is exemplified by melittin, the lipopeptides, and others (40,77,83). This perturbation is observed via dye leakage assays and depolarization studies, which indicate the free transfer of small molecules through the lipid bilayer (16).…”
Section: Combining Information From Multiple Antimicrobial Classesmentioning
confidence: 99%
“…Polymyxin B (34) and trichogin (27) possess fatty acid moieties that are known to be integral to their activities. In recent years, development of linear antimicrobial peptides has shifted to ever-shorter peptides for synthetic and pharmacological reasons (15,17,18,22,23), but relatively little work has investigated linear AMPs with hydrophobic tails. Fatty acid tails have been attached to linear antimicrobial peptides that are not normally acylated (4,(19)(20)(21), in some cases endowing inactive cationic peptides with antimicrobial activity.…”
mentioning
confidence: 99%